THE ROLE OF DIGITAL DENTISTRY IN IMPLANTOLOGY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The integration of digital technologies has fundamentally transformed contemporary implant dentistry, influencing diagnostic accuracy, treatment planning, surgical execution, and prosthetic rehabilitation. Digital dentistry—including cone-beam computed tomography (CBCT), intraoral scanning, computer-aided design and manufacturing (CAD/CAM), and computer-guided implant surgery—has enabled a shift toward more precise, predictable, and minimally invasive implant workflows. However, the clinical relevance and outcome-based advantages of digital implantology compared with conventional approaches remain a subject of ongoing scientific investigation.